Evaluation of the Efficiency of Advanced Oxidation Process Based on Catalytic Ozonation in the Presence of Synthesized Zinc Oxide (Zno) Nanoparticles in the Removal of Volatile Organic Compounds (Vocs) in Polluted Air - Amir Shojaei; Hossein Ghafourian; Linda Yadegarian; Kamran Lari; Mohammadtaghi Sadatipour (Mashhad University of Medical Sciences, 2021)
Abstract Background and Aim :The release of volatile organic compounds from stationary and mobile sources increases the concentration of these compounds in the environment. These compounds are potentially hazardous to the environment and human health. The selection of management and engineering systems has become essential for controlling the release of these pollutants. The aim of this study was to use an advanced catalytic ozonation process to reduce the concentration of these pollutants in industrial emissions. Materials and Methods:In this experimental study, the ozonation process in the presence of a catalyst bed containing ZnO nanocomposites coated on zeolite was used to treat the air contaminated with BTEX compounds as indicators of volatile organic compounds on a laboratory scale. In this study, the synthesis of nanocomposites was done using the chemical co-deposition method. SEM, XRD, BET, and FT-IR analyses were performed to investigate the structural properties of the nanocomposites. The initial concentrations of BTEX (50-200 ppm), the flow of the polluted air (5-20 l/h), humidity (0-75%), and ozone dose (0.25-1 g/h) were studied. The concentration of the BTEX compounds was measured by a Gas Chromatography (GC) device according to the NIOSH Guideline 1501. Results:The results of SEM, XRD, BET, and FT-IR indicated the proper synthesis of nanocomposites. Based on the laboratory results, the optimal process conditions were the initial concentration of pollutants equal to 50 ppm, the inlet flow rate of polluted air equal to 5 l/h, relative humidity of 25-35%, and the inlet concentration of ozone equal to 1 g/h. Under these conditions, the removal efficiencies of benzene, toluene, ethylbenzene, and xylene were 98, 96, 92, and 91%, respectively. Simple ozonation and adsorption processes had lower efficiencies than catalytic ozonation and the synergistic effect of the process was evident. Conclusion:Based on the obtained results, the process has the ability to reduce the concentration of BTEX compounds to the specified standards. This process can be used to treat polluted air in BTEX emitting industries that threaten human health and the environment. Article type:Research article Keywords: Volatile Organic Compounds; BTEX; Nanocomposite; Zinc Oxide; Ozone; Polluted Air